D4.3 Report of the 3rd summer school - Lasaponara, Rosa; Masini, Nicola; Catapano, Ilaria; Soldovieri, Francesco; Agapiou, Athos; Lysandrou, Vasiliki; Christofe, Andreas; Hadjimitsis, Diofantos G. (My University, 2018)
The specific deliverable summarizes the material related to the 3rd Summer School of the project entitled “Geophysics applied to Cultural heritage monitoring”. The deliverable contains actions completed prior the accomplishment of the Summer School acted during September 2018. The current report provides an overview of the event, such as the agenda, all material delivered during the Summer School (e.g. presentations, supportive documents etc.), the list of participants and pictures from the event. Also, some preliminary results and measurements are provided.
Keywords: Geophysics; Cultural heritage monitoring